Pengaruh Green Marketing terhadap Pembelian Ulang pada Produk Brand Avoskin - Yeni Khoirotul Janah; Rusdi Hidayat Nugroho (Universitas Jember, 2023)
As public awareness of a sustainable environment grows in this century, several corporate organizations have begun to implement the sustainability principle in carrying out their firm activities. One of them is a marketing firm that uses a green marketing strategy. This will almost probably alter purchasers' motivation to consume a product repeatedly. The goal of this study is to learn about and investigate the concurrent and partial effects of green marketing, which comprises green product, green price, green promotion, and green location, on repurchasing items from the Avoskin brand in Surabaya. 100 respondents were sampled. Multiple linear regression analysis was utilized to process this data, which was supported by the SPSS 25.0 software. The study's findings indicate that green marketing has a favorable and significant impact on the simultaneous repurchase of Avoskin products in Surabaya. Keywords: Marketing, Green Marketing, Repurchase